Cessation of intravaginal practices to prevent bacterial vaginosis: a pilot intervention in Zimbabwean women. (29th October 2014) - Esber, Allahna; Moyo, Precious; Munjoma, Marshall; Francis, Shelley; van de Wijgert, Janneke; Chipato, Tsungai; Turner, Abigail Norris
Abstract : Objectives: Intravaginal practices—including behaviours such as washing with soap or other materials, using fingers or cloth, or insertion of herbs, powders or other products to dry, cleanse or 'tighten' the vagina—may increase women's risk of bacterial vaginosis by disrupting the vaginal microbiota. In Zimbabwe, intravaginal practices are common. The objective of this study was to assess the feasibility of an intervention based on the transtheoretical model of behaviour change (also called the 'stages of change' model) to encourage cessation of vaginal practices among a sample of Zimbabwean women. Methods: We conducted a 12-week behaviour change intervention to encourage cessation of intravaginal practices (other than cleansing with water) among 85 Zimbabwean women who reported these practices. Results: Self-reported intravaginal practices declined significantly over follow-up, with 100% of women reporting at least one intravaginal practice at enrolment compared with 8% at the final visit. However, we found no significant effect of this reduction on bacterial vaginosis prevalence in unadjusted or adjusted multivariable models (adjusted prevalence ratio for any practice vs none: 0.94, 95% CI 0.61 to 1.43). Conclusions: While the intervention was successful in reducing women's self-reported engagement in intravaginal practices, we observed no corresponding benefit to vaginal health.